Extracurricular Program Evaluation of Memorizing the Quran Tahfiz Class - Widyawati, Widyawati; Mania, St; Akbar, Muh Nur (BASICA, 2025)
This evaluation study aims to evaluate the extracurricular program of reading the Qur'an at MIN Bone through a qualitative approach where the data is sourced from the results of interviews, documentation, and observations, which are then analyzed by reducing, presenting, and verifying the data, then drawing it into a final conclusion. The results show that the context aspect is stated to have met the needs of MIN 1 Bone students and received adequate resource support, so this program is said to have run well. Various criteria set in the input aspect have also been met, such as the availability of facilities and infrastructure, the competence of program supervisors, and the number of students participating in the program to be considered running well. However, the process aspect is considered quite good because there are still obstacles, especially student discipline. Meanwhile, several main objectives of the program cannot be realized optimally in the product aspect where the total number of students who have successfully memorized the Qur'an is still low compared to the number of program participants so this aspect is considered less good. Therefore, improvements are needed to implement the program to achieve the desired goals.